The organisation of childcare: The functions and cooperation between municipalities and counties - Žalimienė, Laimutė (Socialinė teorija, empirija, politika ir praktika, 2003)
The functions of municipalities and counties and cooperation in the area of childcare are analysed in the paper. The analysis is based on the research “The evaluation of organizations in the area of childcare and special education in counties and municipalities” data. The survey and documents analysis were employed in order to gather data. The data analysis suggests that the functions of counties are narrow, sufficient for the effective organisation of childcare, the child rights protection service is not sufficient and efficient and municipalities do not develop the childcare system.
Keywords: Childcare; Municipality; County; Child rights protection service